THE USE OF SOCIO-ECONOMIC ASPECTS AS A TOOL AFFECTING THE SECURITY AND STABILITY OF SOCIETY - Surkovsky, Jozef (PEOPLE: International Journal of Social Sciences, 2024)
Socio-economic aspects are nowadays one of the most important factors for the safety and stability of society. According to them, the possibility of the emergence of pathogenic anomalies threatening the stability of society can be predicted. Based on this fact, it is possible to implement preliminary measures to prevent the occurrence of extraordinary events well in time´s advance. The given theory can be demonstrated on the models of E.W. Burgess concentric zonal structure of the city and on Harris & Ullman multi-core model of the city. Thanks to knowledge from sociology and safety engineering we can to present, how the security and stability of society in a given location can be moved to a higher level, if we know very wel socio-economic aspects of society.